A best proximity point theorem for special generalized proximal β-quasi contractive mappings - M. Iadh Ayari (SpringerOpen, 2019)
Abstract In this paper, we obtain some best proximity point results for a new class of non-self mappings T:A⟶B $T:A \longrightarrow B$ called special generalized proximal β-quasi contractive. Our result is illustrated by an example. Several consequences are derived.